(untitled) (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to determine the effect of media on the growth of fungi fusarium oxysforum and Fusarium oxysforum fungal attack on the stem of the Aloes. The research was conducted through 2 stages, namely the breeding stage conducted at the silviculture Laboratory of the Forestry Department and the application stage conducted in Ariate Village, Huamual District, West Seram Regency. The research time is 6 months from January-September 2024. This study used a complete randomized design (RAL), consisting of 1 treatment with 4 levels of inoculants, with 3 repetitions, each treatment A1=inoculant ( potato water and white sugar ), A2= inoculant ( potato water and brown sugar), A3= inoculant (rice water and white sugar), A4= inoculant (rice water and brown sugar). This study used ANOVA to test the effect of the treatment given to the growth and development of fusarium oxysforum fungi . The results of this study showed that the treatment of a1,a2,a3 and A4 can be used as a medium for the growth of fungal colonies fusarium oxysforum. the 4 growing media treatments did not give a significant effect on the speed of colony growth speed of spread, attack length, attack width, color and aroma of clover on plants.